Cross-border transports and cross-border mobility in EU border regions - Medeiros, E. (2020)
Administrative boundaries create all sorts of barriers. These include obstacles associated with cross-border mobility. The presence of cross-border transports can be pivotal to reducing the barrier-effect on citizen's mobility and to increasing territorial integration of the European Union (EU). As recent surveys have revealed, cross-border accessibility is still considered a major barrier across most EU borders. In this context, this paper examines the overall current panorama of cross-border transports in the EU as a crucial barrier, whilst proposing a Cross-border Transport Permeability index to allow comparing this barrier across the EU. The findings indicate that cross-border transports are not yet sufficiently developed in the face of the increasing needs of EU citizens to cross borders, even in the most mature and socio-economically developed EU border areas, and that complex legal and administrative frameworks from both sides of the border make the creation of joint solutions for improving cross-border transportation across EU borders a challenging task.